A new second-order upper bound for the ground state energy of dilute Bose gases - Giulia Basti; Serena Cenatiempo; Benjamin Schlein (Forum of Mathematics, Sigma, 2021)
We establish an upper bound for the ground state energy per unit volume of a dilute Bose gas in the thermodynamic limit, capturing the correct second-order term, as predicted by the Lee–Huang–Yang formula. This result was first established in [20] by H.-T. Yau and J. Yin. Our proof, which applies to repulsive and compactly supported